2018
DOI: 10.1016/j.jclinepi.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Between-trial heterogeneity in meta-analyses may be partially explained by reported design characteristics

Abstract: ObjectiveWe investigated the associations between risk of bias judgments from Cochrane reviews for sequence generation, allocation concealment and blinding, and between-trial heterogeneity.Study Design and SettingBayesian hierarchical models were fitted to binary data from 117 meta-analyses, to estimate the ratio λ by which heterogeneity changes for trials at high/unclear risk of bias compared with trials at low risk of bias. We estimated the proportion of between-trial heterogeneity in each meta-analysis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Several reasons support the use of at least one high risk of bias assessment as the definition for inadequate methods. Some risk of bias domains might translate into more statistical bias than others, but empirical evidence on the relative importance of the risk of bias domains is limited, and the effect of several versus one high risk assessment on research outcomes is unknown 32 33. The empirical relationship between risk of bias assessments and research outcomes (including actual statistical bias) requires further research.…”
Section: Methodsmentioning
confidence: 99%
“…Several reasons support the use of at least one high risk of bias assessment as the definition for inadequate methods. Some risk of bias domains might translate into more statistical bias than others, but empirical evidence on the relative importance of the risk of bias domains is limited, and the effect of several versus one high risk assessment on research outcomes is unknown 32 33. The empirical relationship between risk of bias assessments and research outcomes (including actual statistical bias) requires further research.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of bias-related reporting characteristics of studies included in meta-analyses such as blinding, random sequence generation, allocation concealment or other reporting related items was not assessed. Although empirical evidence from medical research has shown that between-study heterogeneity may be partially explained by the reporting of characteristics responsible for bias [26], this was beyond the scope of the present work and it may constitute ground for future research. Table 4.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, there was some significant heterogeneity between included studies. This discrepancy could have occurred as a result of the heterogeneity of patient characteristics such as age and disease severity, comorbidities, methods for diagnosis and evaluation, treatment doses and interval, and study design features [40][41][42][43].…”
Section: Confidence Intervalmentioning
confidence: 99%